A systematic review of randomized controlled trials assessing phytochemicals and natural ingredients for skin and hair care - Samar Thiab, Nizar M. Mhaidat, May Abu Taha, Sarah Thiab, Somaya Koraysh, Reem Abutayeh, Iman Basheti (Journal of Applied Pharmaceutical Science, 2021)
Cosmetics are marketed and used worldwide for various purposes. Several natural products are used for the development of cosmetic preparations. This paper systematically reviews randomized controlled trials (RCTs) investigating plant extracts, herbal preparations, and isolated plant-derived compounds used particularly for skin and hair care. Two independent electronic searches were conducted through PubMed and EMBASE to identify eligible RCTs. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement was followed. Data extraction was performed independently by four authors based on standardized extraction forms. The risk of bias was assessed using the Cochrane Collaboration’s tool for assessing the risk of bias in randomized trials. Sixty-three RCTs were identified; 53 were using natural products for skin care and 10 for hair care. The results were summarized in tables including the population, type of intervention, comparisons with placebo or other natural products, outcomes reported, follow-up period (P: Patient, Population; I: Intervention; C: Comparison (or Control); O: Outcome; T: Time), and country in which the study was conducted. Ten plants were identified to be present in different locations in Jordan by referring to the Royal Botanic Gardens’ publication, titled “The Plants of Jordan: An Annotated Checklist.” Some plants were found to have promising findings requiring further investigations in bigger RCTs with robust design and adequate reporting.
Keywords: Skin care, hair care, natural cosmetics, randomized controlled trials.